Estudio de factibilidad para la creación de una bolsa virtual de carga en la ciudad de Armenia y Cali (2013)
Intermediation activity in land freight transportation has been conducted informally by commission agents, who do not make a careful monitoring to the transporters and load generating companies. The virtual space is a practical and innovative tool to the transporters and load generators, so trough this, it could be established a direct communication, and prices will be improved to the transporters who will save money avoiding commissions, which in most cases are very high.